High-Level Service Connectors for Component-Based High Performance Computing - Carvalho-Junior, Francisco Heron de; Correa, Ricardo Cordeiro; Araujo, Gisele Azevedo; Silva, Jefferson Carvalho; Lins, Rafael Dueire (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2007)
Component-based programming has been applied to address the requirements of applications in high performance computing (HPC). The usual service connectors of commercial component models do not fit some requirements of HPC, mainly regarding the support of parallelism, however. This paper looks at extensions to the usual notion of service connector to meet such requirements, using the # component model as a substratum, evidencing its expressiveness.